Who Benefits from Promoting Small Enterprises? Some Empirical Evidence from Ethiopia - Rijkers, Bob; Ruggeri Laderchi, Caterina; Teal, Francis (2012)
The Addis Ababa Integrated Housing Development Program (AAIHDP) aims to tackle the housing shortage and unemployment that prevail in Addis Ababa by deploying and supporting small enterprises to construct low-cost housing using technologies novel for Ethiopia. The motivation for such support is predicated on the view that small firms create more jobs per unit of investment by virtue of being more labor intensive and that the jobs so created are concentrated among the low-skilled and hence the poor. To assess whether the program has succeeded in biasing technology adoption in favor of labor and thereby contributed to poverty reduction, the impact of the program on technology usage, labor intensity, and earnings is investigated using a unique matched workers-firms dataset, the Addis Ababa Construction Enterprise Survey (AACES), collected specifically for the purpose of analyzing the impact of the program. We find that program firms do not adopt different technologies and are not more labor intensive than nonprogram firms. There is an earnings premium for program participants, who tend to be relatively well educated, which is heterogeneous and highest for those at the bottom of the earnings distribution.